2019
DOI: 10.1038/s41598-018-36947-3
|View full text |Cite
|
Sign up to set email alerts
|

Attentional processes in typically developing children as revealed using brain event-related potentials and their source localization in Attention Network Test

Abstract: Attention-related processes include three functional sub-components: alerting, orienting, and inhibition. We investigated these components using EEG-based, brain event-related potentials and their neuronal source activations during the Attention Network Test in typically developing school-aged children. Participants were asked to detect the swimming direction of the centre fish in a group of five fish. The target stimulus was either preceded by a cue (centre, double, or spatial) or no cue. An EEG using 128 ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 67 publications
(173 reference statements)
1
14
0
Order By: Relevance
“…Previous functional MRI and electroencephalography (EEG) studies have investigated ANT associated brain activity among both adults (Fan et al, 2005, Galvao-Carmona et al, 2014Neuhaus et al, 2010) and children (Konrad et al, 2005, Gopalan et al, 2019, and have reported that the different attentional networks recruits different brain regions. Executive control has been associated with activity in the anterior cingulate and bilateral prefrontal cortical regions (Fan et al, 2005;Konrad et al, 2005), orienting with activity in bilateral superior parietal cortical regions, and alerting with activity in thalamic, inferior parietal and prefrontal cortical regions (Fan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Previous functional MRI and electroencephalography (EEG) studies have investigated ANT associated brain activity among both adults (Fan et al, 2005, Galvao-Carmona et al, 2014Neuhaus et al, 2010) and children (Konrad et al, 2005, Gopalan et al, 2019, and have reported that the different attentional networks recruits different brain regions. Executive control has been associated with activity in the anterior cingulate and bilateral prefrontal cortical regions (Fan et al, 2005;Konrad et al, 2005), orienting with activity in bilateral superior parietal cortical regions, and alerting with activity in thalamic, inferior parietal and prefrontal cortical regions (Fan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The orienting network in fMRI studies with adults has shown neuronal activity in the TPJ, bilateral superior parietal lobe, FEFs, pulvinar, and superior colliculus (Fan et al, 2005;Konrad et al, 2005;Xuan et al, 2016). Previous ANT studies with children found orienting network responses in the superior frontal gyrus and bilaterally in the occipital cortex (Konrad et al, 2005;Santhana Gopalan et al, 2019). A previous fMRI study also showed that children with ADHD have atypical activation in the frontostriatal region compared to control children (Bellman, 2002, 104).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of neuronal-level brain information related to ANT in children with AP and children with RD in the same study. In this study, we examined reaction time (RT) performance, scalp topography of event-related potentials (ERPs), and their neuronal sources associated with attention network sub-processes using an Attention Network Test (ANT) (Santhana Gopalan et al, 2019) in AP and RD children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 , 11 In contrast, typically developing children demonstrate developmental differences during inhibitory processing with activation of more central and posterior regions (premotor cortex, superior temporal gyrus, bilateral parietal and occipital cortices) relative to inferior and medial frontal gyri and ACC, potentially suggesting the inhibitory network is slower to develop in frontal areas. 12 , 13 …”
Section: Introductionmentioning
confidence: 99%